Factors Associated with Pain in Palliative Patients and the Role of Spiritual Services in Pain Management - Hamzah Shatri; Rudi Putranto; Cosphiadi Irawan; Mizanul Adli; Ratih Arianita Agung; Vera Abdullah; Dina Elita (Acta Medica Indonesiana)
Background: pain is one of the most often symptoms experienced by patients with advanced or chronic diseases which can cause a decrease in the quality of life of palliative patients. Pain in palliative patients has not yet received enough attention, especially factors associated with pain and its management. This study aimed to determine the factors associated with pain in palliative patients and also assess whether there is a two-way relationship between psychological factors and pain. In addition, we will also see whether spiritual services play a role in relieving pain. Methods: cross-sectional study were used and secondary data were obtained from medical records of 285 palliative patients at Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia. The data were processed to determine the psycho-socio-demographic characteristics, the reciprocal relationships of psychological and pain aspects, and the relationship of pharmacological therapy (opioids), non-pharmacological therapy (spiritual services), and combination of both therapies in pain management. Results: of the 285 palliative patients, 60.3% had pain, which was found more in cancer patients (74.4% vs 25.6%). Pain was found more in patients aged 41-60 years (51.1%), women (51.2%), and unemployed (30.2%). The severity of the pain was found to be significant in patients with depressive symptoms (p=0.045), while patients with anxiety symptoms (p=0.155) and sleep disorders (p=0.619) had no significant relationship. Pain experienced by palliative patients was not statistically significant in causing depression (p=0.058), anxiety (p=0.107), and sleep disorder (p=0.639). Moreover, pain management with opioids, spiritual services, or combination of them turned out to have significant results (p=0.022). Conclusion: pain in palliative patients is mainly experienced by cancer patients and the elderly. Psychological factors affect the condition of pain, so the management that includes biopsychosocial aspect will be able to reduce pain significantly.